1999
DOI: 10.1101/gad.13.4.449
|View full text |Cite
|
Sign up to set email alerts
|

ELAV tumor antigen, Hel-N1, increases translation of neurofilament M mRNA and induces formation of neurites in human teratocarcinoma cells

Abstract: Human ELAV proteins are implicated in cell growth and differentiation via regulation of mRNA expression in the cytoplasm. In human embryonic teratocarcinoma (hNT2) cells transfected with the human neuronal ELAV-like protein, Hel-N1, neurites formed, yet cells were not terminally differentiated. Cells in which neurite formation was associated with Hel-N1 overexpression, also expressed increased levels of endogenous neurofilament M (NF-M) protein, which distributed along the neurites. However, steady-state level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
187
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(199 citation statements)
references
References 58 publications
(105 reference statements)
12
187
0
Order By: Relevance
“…2B), although whether HuD binds to the NF-H mRNA has yet to be determined. Thus, as was suggested recently, neurone-speci®c Hu proteins are likely to be involved in the translational up-regulation of speci®c AREcontaining mRNAs, which encode proteins that are critical for neuronal differentiation (Antic et al 1999). Moreover, our data also suggest the involvement of mRNA export from the nucleus to the cytoplasm in the function of neurone-speci®c Hu proteins.…”
Section: The Novel Nes Of Hud and The Nucleocytoplasmic Shuttling Of supporting
confidence: 84%
See 3 more Smart Citations
“…2B), although whether HuD binds to the NF-H mRNA has yet to be determined. Thus, as was suggested recently, neurone-speci®c Hu proteins are likely to be involved in the translational up-regulation of speci®c AREcontaining mRNAs, which encode proteins that are critical for neuronal differentiation (Antic et al 1999). Moreover, our data also suggest the involvement of mRNA export from the nucleus to the cytoplasm in the function of neurone-speci®c Hu proteins.…”
Section: The Novel Nes Of Hud and The Nucleocytoplasmic Shuttling Of supporting
confidence: 84%
“…7). Consistent with this, the repression of human HuB expression by HuB antisense RNA has been shown to result in the inhibition of retinoic acidinduced neuronal differentiation of hNT-2 cells (Antic et al 1999). In addition, it has recently been shown that the inhibition of HuD expression by the HuD antisense oligonucleotides severely inhibits NGF-induced neurite outgrowth in PC12 cells (Dobashi et al 1998;ArandaAbreu et al 1999).…”
Section: Is the Initiation Of Neuronal Differentiation Dependent On Hmentioning
confidence: 82%
See 2 more Smart Citations
“…Approximately 5%8% of human protein-coding genes contain AREs, suggesting the overall importance of Hu proteins in regulating mRNA stability [54,59]. In addition to mRNA stability, Hu proteins also regulate translation by acting as either enhancers or repressors of translation of their target genes, including neurofilament M, hypoxia inducible factor 1a and CD83 [56,60,61]. In the nucleus, Hu proteins serve as regulators of polyadenylation and alternative splicing [62].…”
Section: Hu/elavl Protein Familymentioning
confidence: 99%